Making projects work : effective stakeholder and communication management - Bourne, Lynda (Best practices and advances in program management series., 2015)
This book provides a framework for understanding and managing factors required for achieving successful project and program outcomes. It presents guidelines to help readers develop an understanding of governance and its connection to strategy as the starting point for decisions on what work needs to be done. The book describes how to craft appropriate communication strategies to develop and maintain successful relationships with stakeholders. It highlights the strengths and weaknesses of existing project controls and outlines effective communication techniques for managing expectations and ac.